Virtual Reality Exposure Therapy for Fear of Heights: Clinicians’ Attitudes Become More Positive After Trying VRET - Rimer, Elise; Husby, Lars Vågsholm; Solem, Stian (Frontiers in Psychology, 2021)
Background: Virtual reality exposure therapy (VRET) has the potential to solve logistic challenges when treating specific phobias. However, VRET has yet to see a large-scale implementation in clinical settings despite positive findings in treatment trials. This may partly be due to attitudes and lack of experience among clinicians, but also because of expensive and stationary VR solutions. Objective: This study tested whether modern, wireless, commercially available VR equipment with controller-free hand tracking could induce and reduce discomfort using scenarios designed for fear of heights. Also, the study tested if clinicians’ attitudes toward using VR in therapy changed after trying it themselves. Method: Attitudes to using VR in therapy and discomfort ratings were assessed for 74 clinicians before and after completing two VR scenarios. In addition, 54 non-clinicians completed the same scenarios. Participants were not diagnosed with acrophobia. Results: The VR scenarios induced discomfort comparable to participants' reported fear of heights in real life. Repeated training reduced discomfort. Positive attitudes toward use of VR in therapy was predicted by previous experience with VR, as well as positive attitudes toward novel technology and exposure therapy. Clinicians’ attitudes became more favourable after trying VRET themselves. Clinicians reported a range of possible advantages and disadvantages of using VR in therapy. Conclusion: VRET for fear of heights was able to induce and reduce discomfort in clinicians and non-clinicians, and clinicians' attitudes toward using VRET become more positive after trying VRET for themselves. The latest generation of VR solutions has potential to improve clinical availability and treatment options. Future research should explore how VRET can be implemented in clinical settings.